2019
DOI: 10.1007/s00127-019-01748-0
|View full text |Cite
|
Sign up to set email alerts
|

Minding the treatment gap: results of the Singapore Mental Health Study

Abstract: Purpose To establish the 12-month treatment gap and its associated factors among adults with mental disorders in the Singapore resident population using data from the second Singapore Mental Health Study and to examine the changes since the last mental health survey conducted in 2010. Methods 6126 respondents were administered selected modules of the Composite International Diagnostic Interview, to assess major depressive disorder (MDD), dysthymia, bipolar disorder, generalized anxiety disorder (GAD), obsessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 37 publications
2
57
0
5
Order By: Relevance
“…A rather local determinant of stigma is perhaps the “elitism mindset among Singaporeans” which may be related to meritocracy. In an earlier study pertaining to the treatment gap in Singapore, Subramaniam et al (2019) discussed how meritocracy is highly regarded in Singapore and that people with higher education face greater inertia towards seeking treatment in order to conform to societal expectations [ 56 ]. In Yang et al [ 57 ] study which was guided by a framework of “what matters most”, it was highlighted that mental illness stigma was contingent on the degree to which participants were able to achieve “what matters most” in their cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…A rather local determinant of stigma is perhaps the “elitism mindset among Singaporeans” which may be related to meritocracy. In an earlier study pertaining to the treatment gap in Singapore, Subramaniam et al (2019) discussed how meritocracy is highly regarded in Singapore and that people with higher education face greater inertia towards seeking treatment in order to conform to societal expectations [ 56 ]. In Yang et al [ 57 ] study which was guided by a framework of “what matters most”, it was highlighted that mental illness stigma was contingent on the degree to which participants were able to achieve “what matters most” in their cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…The Singapore Mental Health Study (SMHS) 2016 was a nationwide study, where one of the aims was to investigate the treatment gap for mental disorders in Singapore. The SMHS 2016 showed that among the population who had the highest treatment gap were those with tertiary level education [21]. Individuals in tertiary institutions have a special significance as they represent a large number of people who are at an age when mental disorders first present (onset) and may have lasting implications if not treated properly [22].…”
mentioning
confidence: 99%
“…Thus, those pursuing tertiary education are most likely to face pressures to be high-achieving and resilient. They may fear being perceived otherwise once assigned a diagnosis and prefer to deal with the problem on their own [21].…”
mentioning
confidence: 99%
“…Online support groups in the form of internet support groups and chat rooms may offer a valuable source of information and social support for those with mental health problems, particularly mood and anxiety problems. Recent evidence suggests that the wide treatment-seeking gap for mental health continues to pose a local public health challenge [ 48 ]. Hence, online support groups could guide individuals to seek professional help for their mental health problems; in addition, they could complement the formal treatment services that patients may receive.…”
Section: Discussionmentioning
confidence: 99%